2008
DOI: 10.1016/j.molcel.2008.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Intersubunit Rotation in Single Ribosomes

Abstract: During the elongation cycle, tRNA and mRNA undergo coupled translocation through the ribosome catalyzed by elongation factor G (EF-G). Cryo-EM reconstructions of certain EF-G-containing complexes led to the proposal that the mechanism of translocation involves rotational movement between the two ribosomal subunits. Here, using single-molecule FRET, we observe that pretranslocation ribosomes undergo spontaneous intersubunit rotational movement in the absence of EF-G, fluctuating between two conformations corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

90
597
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 385 publications
(694 citation statements)
references
References 51 publications
90
597
5
Order By: Relevance
“…1), consistent with the ability of the ribosome to undergo spontaneous intersubunit rotational movement (26). Interestingly, RMSDs between separately refined structures of the 70S ribosome-RF1 complex also correlate with anisotropic temperature factors derived from a lower-resolution structure of a 70S ribosome-tRNA complex by TLS refinement and obtained in a different crystal form (27), suggesting that the large-scale dynamic properties of the ribosome are similar for these complexes.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…1), consistent with the ability of the ribosome to undergo spontaneous intersubunit rotational movement (26). Interestingly, RMSDs between separately refined structures of the 70S ribosome-RF1 complex also correlate with anisotropic temperature factors derived from a lower-resolution structure of a 70S ribosome-tRNA complex by TLS refinement and obtained in a different crystal form (27), suggesting that the large-scale dynamic properties of the ribosome are similar for these complexes.…”
Section: Resultssupporting
confidence: 62%
“…The cross-crystal averaged maps appeared most ''improved'' (23) when 3-fold aver- (24). (A and B) A-weighted Fobs Ϫ Fcalc difference maps calculated using phases from the 2.8 Å model (26) and structure factors from the 3.7 Å data (24) clearly show the presence of helix 78 of 23S rRNA (A) and protein L36 (B), which were reported as disordered or absent in the 2.8 Å structure and in the cross-crystal averaged maps (23). The absence of any potential bias from the 3.7 Å model suggests that the cross-crystal averaged maps were biased toward the stronger 2.8 Å dataset.…”
Section: Evaluating Differences Between 28 å and 37 å Structures Ofmentioning
confidence: 99%
“…Because the ribosomes captured in our snapshots were not engaged in protein synthesis, lacking mRNA and aminoacylated tRNAs, we must assume that their idle motions in the thermal environment sample the conformational space permitted by the degrees of freedom, thus exhibiting the conformational changes that would be productive in the presence of the ligands of the translational machinery (mRNA, aa-tRNA, eEF2, and eEF1A). Indeed, idling of the pretranslocational ribosome in the absence of elongation factors along the direction of the most prominent conformational changes (intersubunit motion and opening/ closing of L1 stalk) has been previously observed by singlemolecule FRET (8,9) and cryo-EM (33). Idling of the empty ribosome along the same path has also been inferred from a series of X-ray structures (34).…”
Section: Discussionmentioning
confidence: 75%
“…In some cases, however, snapshots of major ribosomal regions with large conformational flexibility have defied classification into discrete states altogether, even by the most advanced analytical methods (7). Single-molecule FRET experiments have yielded evidence for discrete conformational changes in single, freely equilibrating pretranslocational ribosomes, and provided ensemble averages for such changes, but have been unable to provide data for short-lived intermediates (8,9).…”
mentioning
confidence: 99%
“…However, bulk FRET studies suggested that hybrid states coupled to the ratchet-like motion may form spontaneously, i.e., without binding EF-G (9,10). Further evidence for spontaneous ratcheting was provided by single-molecule FRET studies, which showed individual pretranslocation ribosomes oscillating between the nonrotated and the rotated states (4). Also the tRNAs were observed to fluctuate between classic and hybrid states in dynamic equilibrium (11), possibly sampling through additional intermediate states.…”
mentioning
confidence: 99%